FUNCTIONS OF STATE-ADMINISTRATIVE AND MILITARY TITLES OF THE YENISEI KYRGYZ: TUTUK, SANGUN (TUO-TUOK, SANGGUN) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
This article analyzes the origin, formation and distribution area of previously littleexplored in science, but widespread state, administrative and military titles (positions) «tutuk»(«tutuk») and «sangun» («sangun») in the Kyrgyz Kaganate (VI- XI centuries) and other stateformations of the Eurasian space. For the first time, an attempt has been made to make a historicaland linguistic analysis of previously unexplored titles (positions) used in the management of thestate and its structures. From the first steps of state history, Kyrgyz society was strictly ranked. Theplace and political weight of a member of society was largely determined by his title, often hereditary,which consolidated the position of his bearer in the system of social ties and subordination. In thesystem of state administration, the Kyrgyz and their neighbors, the Kok Turks, Uighurs and otherpeoples, had a bureaucratic apparatus for governing the country and its possessions that was quitedeveloped for its time. High government positions, various administrative units of the state weregoverned by officials with different titles.
Keywords: tutuk, sangun, titles, Yenisei Kyrgyz, ancient Turks, Kyrgyz Kaganate, runic writing, Tang China.